Minat Siswa Kelas III, IV dan V Sd Muhammadiyah Cilopadang Terhadap Ekstrakurikuler Renang - Setiawan, Jefri Anton; Imam S, Dian; Kusmiyati, Kusmiyati (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the level of student interest in swimming extracurricular activities at SD Muhammadiyah Cilopadang. This study uses a quantitative descriptive method with a questionnaire as the main instrument for data collection. The research subjects were students in grades III, IV, and V who participated in swimming extracurricular activities. The data obtained were analysed descriptively to describe the level of student interest based on predetermined categories. The results showed that most students had a very high level of interest in swimming activities. Specifically, student interest was in the Very High category (31.1%), High (28.9%), Fair (24.4%), and Low (15.6%). These findings indicate that swimming extracurricular activities are popular among the majority of students, even though their implementation still faces obstacles in the form of limited facilities, infrastructure, and the number of coaches available.